1992
DOI: 10.1038/358242a0
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear localization and signalling activity of phosphoinositidase Cβ in Swiss 3T3 cells

Abstract: The hydrolysis of phosphatidylinositol 4,5-bisphosphate (PtdInsP2) is a widespread receptor-coupled signalling system at the plasma membrane of most eukaryotic cells. The existence of an entirely separate nuclear phosphoinositide signalling system is suggested from evidence that purified nuclei synthesize PtdInsP2 and phosphatidylinositol 4-phosphate (PtdInsP) in vitro and that a transient decrease in the mass of these lipids occurs when Swiss 3T3 cells are cultured in the presence of insulin-like growth facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
228
2
2

Year Published

1995
1995
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 323 publications
(241 citation statements)
references
References 27 publications
9
228
2
2
Order By: Relevance
“…It has been proposed that phosphatidylinositol-transfer proteins deliver phosphatidylinositol to lipid kinases to yield phosphatidylinositol 4,5-biphosphate (PIP2) as a substrate for PLC-␤ (Thomas et al, 1993). It has also been shown that the enzymes responsible for the metabolism of inositol lipids and present in the nuclei of several cell types are the ␤1-and ␤2-isoforms of PLC (Martelli et al, 1992;Divecha et al, 1993b;Zini et al, 1993Zini et al, , 1994Bertagnolo et al, 1997). PLC-␤1 has been demonstrated in mouse oocytes by using polymerase chain reaction (Dupont et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that phosphatidylinositol-transfer proteins deliver phosphatidylinositol to lipid kinases to yield phosphatidylinositol 4,5-biphosphate (PIP2) as a substrate for PLC-␤ (Thomas et al, 1993). It has also been shown that the enzymes responsible for the metabolism of inositol lipids and present in the nuclei of several cell types are the ␤1-and ␤2-isoforms of PLC (Martelli et al, 1992;Divecha et al, 1993b;Zini et al, 1993Zini et al, , 1994Bertagnolo et al, 1997). PLC-␤1 has been demonstrated in mouse oocytes by using polymerase chain reaction (Dupont et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…SDS-polyacrylamide gel electrophoresis followed by autoradiography revealed a major labeled band of 58 kDa corresponding, as observed in vitro phosphorylation, to the high molecular weight form of TdT (Fig. 3, [31,32] and can be downregulated in KM-3 cells after 24 h of PMA treatment (pers. data).…”
Section: Resultsmentioning
confidence: 56%
“…Since TdT and PKC colocalize in the interchromatin domains ( [12,15,23,[29][30][31][32][33] and pers. data), we tested TdT as a substrate for PKC.…”
Section: Resultsmentioning
confidence: 99%
“…2. 3.1. Nuclear phospholipase C-β 1 IGF-mediated PtdIns(4,5)P 2 hydrolysis and DAG generation in membrane-depleted nuclei of Swiss 3T3 cells pointed to the possible involvement of phospholipase C (20), and the activation of the nuclear PI-PLC-β 1 in response to IGF-I was later confirmed (46,47). In vivo model of regenerating rat liver showed the similar increase in the level of the nuclear DAG 20 hours after partial hepatectomy (5).…”
Section: Nuclear Phospholipase Cmentioning
confidence: 82%
“…IGF-mediated increase in the level of nuclear DAG and the activity of PI-PLC that was described 15 years ago (20,46) When aphidicolin-synchronized HL-60 cells were released from the block and allowed to progress synchronously through the cell cycle, a PI-PLC inhibitor-sensitive increase in the level of DAG was observed in nuclei 8 h after release from the block that corresponded to G 2 /M phase of the cell cycle (68). In addition, the presence of the PI-PLC inhibitor delayed the progression of the cells through G 2 /M phase and correlated with translocation of PKC-βΙΙ that was previously shown to phosphorylate lamins (29,68,71).…”
Section: The Role Of the Nuclear Pi-plc In Differentiation Mitogenesmentioning
confidence: 98%